English Teachers’ Beliefs on Technology Enhanced Language Learning: A Rush Paradigmatic Shift during Covid-19 Pandemic - Yadi Supriadi; Asri Ainun Nisa; Silvia Wulandari (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2020)
Covid-19 pandemic has affected multifaceted aspects of life around the globe, including Indonesia. English language pedagogy is an obvious milieu that suffered from this pandemic, notably English teachers. They should shift their beliefs from traditional to technological paradigm (e.g. online teaching). However, this paradigmatic shift generates challenges for their teaching practices. This study aimed at scrutinizing the paradigmatic shift of English teachers’ beliefs on the deployment of Technology-Enhanced Language Learning (TELL) during this pandemic. A descriptive case study was employed as a research design. There were four English teachers involved as participants. The findings implied that the teachers’ beliefs represent their teaching practices during this Covid-19 pandemic.